THE IMPLEMENTATION OF ERLY INITIATION BREASTFEEDING ON INTRANATAL MOTHER TO DEVELOPE BOUNDING ATTACHMENT IN MOJOKERTO - Rina Rina Mardiyana (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Early initiation of breastfeeding (IMD) is the first time for baby to learn to breastfeed at the first hour of life outside the womb. The warmth of the mother’s breast when the baby is placed on the mother chest, will make the baby feel the vibration of love. Edmond (2006) in Ghana proved breastfeed infants be given a chance in the first hour, and left skin contact with the mother (at least for an hour), it can prevent infant mortality by 22%. Research design using analitytical methods with one shot case study approach. The population is all maternal at TPMB Ny Rindra Deviasti., SST., M.Kes in kalang kalen village, dlanggu subdistrict, Mojokerto regency as many as 12 people. Data collection instrument using checklist an questionnaire. The results showed that of the 12 people who did early breastfeeding initiation (IMD) got 11 people (91,7%) require care support after growing bonding attachment and 1 people (8,3%) require more support after growing bonding attachment. The resuts showed a correlation between the implementation of early initiation of breastfeeding on intra natal mother to develope bonding attachment at TPMB Ny Rindra Deviasti., SST., M.Kes in kalang kalen village, dlanggu subdistrict, Mojokerto regency. With the results of this study are expected to pregnant women to exercise early initiation of breastfeeding after childbirth because it is very beneficial for both mother and baby